1998
DOI: 10.1016/s0741-5214(98)70208-3
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, hemorheologic factors, and progression of peripheral arterial disease in patients with claudication

Abstract: Elevations in rheologic factors may have important effects on further reduction of blood flow in the legs of patients with claudication and promote worsening ischemia and clinical progression of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
4
21
0
1
Order By: Relevance
“…Among traditional risk factors, current smoking appeared to be the most powerful predictor of LV-PAD progression. These data, based on objective measurements, are in line with the majority of [27][28][29][30][31] but not all 22,32,33 studies on the clinical progression of PAD. Smoking cessation is considered a first-line treatment among smokers with PAD.…”
Section: Aboyans Et Al Risk Factors For Pad Progression 2625supporting
confidence: 83%
“…Among traditional risk factors, current smoking appeared to be the most powerful predictor of LV-PAD progression. These data, based on objective measurements, are in line with the majority of [27][28][29][30][31] but not all 22,32,33 studies on the clinical progression of PAD. Smoking cessation is considered a first-line treatment among smokers with PAD.…”
Section: Aboyans Et Al Risk Factors For Pad Progression 2625supporting
confidence: 83%
“…The results of this combined ana lysis were highly consistent [4] and this combined OR is compatible with the known effect of VWF on PVD [68]. In particular, there is evidence that VWF levels are increased in subjects with peripheral arterial disease [69] and that the level of VWF has been shown to be predictive of peripheral artery graft occlusion [70] and, in a prospective cohort of patients with claudication [68], VWF was also predictive of the future development of severe chronic leg ischemia. This association with disease progression that persisted after adjustment for age and sex was partly accounted for by cigarette smoking and severity of disease at baseline.…”
Section: Abo(h) and Arterial Thrombosissupporting
confidence: 78%
“…Despite this, all but one reported a positive OR in relation to non-O blood groups and in meta-ana lysis the OR associated with non-O was 1.45 -with a reasonably narrow 95% CI of 1.35-1.56 [4]. The results of this combined ana lysis were highly consistent [4] and this combined OR is compatible with the known effect of VWF on PVD [68]. In particular, there is evidence that VWF levels are increased in subjects with peripheral arterial disease [69] and that the level of VWF has been shown to be predictive of peripheral artery graft occlusion [70] and, in a prospective cohort of patients with claudication [68], VWF was also predictive of the future development of severe chronic leg ischemia.…”
Section: Abo(h) and Arterial Thrombosissupporting
confidence: 54%
“…58 Hemorheologic factors have been shown to be associated with an increased risk of need for vascular intervention. 116 Patients with premature PAD (onset of symptoms at or before age 45) seem to have more rapid progression of disease and generally poorer outcomes. [117][118][119][120][121] One study suggested that PAD progression in large arteries was related to smoking, the total cholesterol to HDL-C ratio, lipoprotein(a), and high-sensitivity CRP, but only diabetes mellitus was associated with progression in smaller arteries.…”
Section: Progression Of Padmentioning
confidence: 99%